2006
DOI: 10.1029/2005wr004516
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of scour and fill in dryland sand bed streams

Abstract: [1] Spatial patterns of scour and fill in two dryland ephemeral stream channels with sandy bed material have been measured with dense arrays of scour chains. Although the depth and areal extent of bed activity increased with discharge, active bed reworking at particular locations within the reaches resulted in downstream patterns of alternate shallower and deeper areas of scour. The variation was such that mean scour depths for individual cross sections varied about the mean for the reach by a factor of 2-4 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…If the bar is locally elevated with accumulated sediments or depressed, then the overflowing water scours the elevation and fills in the depression (Powell et al, 2005(Powell et al, , 2006. If the bar is located in a curved channel, then the outer side of the channel is eroded and the inner side is accumulated with sediments due to the secondary flows, outwards near the surface and inwards near the bottom (Kalkwijk and Booij, 1986).…”
Section: Effects Of Spates On Erosion and Sedimentation Of The Sandbarmentioning
confidence: 98%
“…If the bar is locally elevated with accumulated sediments or depressed, then the overflowing water scours the elevation and fills in the depression (Powell et al, 2005(Powell et al, , 2006. If the bar is located in a curved channel, then the outer side of the channel is eroded and the inner side is accumulated with sediments due to the secondary flows, outwards near the surface and inwards near the bottom (Kalkwijk and Booij, 1986).…”
Section: Effects Of Spates On Erosion and Sedimentation Of The Sandbarmentioning
confidence: 98%
“…The channel-wide scour and fill patterns indicated by the scour chains of Leopold, Emmett and Myrick (1966) may require a different explanation, perhaps involving plane beds in the upper flow regime. Powell et al (2006) explore the possibility that depth of scour (and subsequent fill) in a sand-bed tributary of Walnut Gulch varies downstream in a fashion that has pseudo-regularity (Figure 13.19(a)). For the larger floods of their record, lozenge-shaped zones of maximum scour appear to have a longitudinal spacing that is about seven times the channel width.…”
Section: Scour and Fillmentioning
confidence: 99%
“…Y is the calculated average flow depth; u is the calculated average flow velocity (afterFoley, 1978). 19 (a) Isopleths of scour along a reach of a sand-bed, headwater tributary of Walnut Gulch, southern Arizona, during four flash floods of varying magnitude showing pseudo-regularity of maximum scour with a downstream spacing of about seven times the channel width (afterPowell et al, 2006). (b) Specific scour volume as a function of unit stream power for reaches of three headwater channels of Walnut Gulch.…”
mentioning
confidence: 99%
“…The variation is such that volumes of scour at individual cross sections differ from the reach mean by a factor of 2-3 in the main-channel and 3-4 in the lower-tributary channel. Powell et al (2006) undertook a detailed geostatistical analysis of the spatial patterns using autocorrelation and semi-variogram techniques. Although the analysis was constrained somewhat by the limited length and inherent noisiness of the data, it suggested that stream-bed activity was not random, at least at moderate to high flows, but varied in a periodic manner along alternate sides of the channels with a wavelength of approximately seven channel widths.…”
Section: Spatial Patterns Of Scour Fill and Channel Changementioning
confidence: 99%
“…To address this problem, we have deployed dense arrays of scour chains in three sand-bed channels in SE Arizona to obtain spatially intensive measurements of scour and fill. Detailed statistical analyses of the variability and spatial pattern of scour and fill for individual events have shown that 1) mean depths of scour and fill increased with event magnitude; 2) populations of scour depths were exponentially distributed and 3) stream-bed activity was highly non-uniform with scour and fill concentrated at certain locations within the reaches, perhaps in response to local differences in shear stress generated by secondary circulations (Powell et al, 2005(Powell et al, , 2006. In this paper, we present an analysis of the volumes of material eroded and deposited within the study reaches in order to examine the relationships between the transfer of sediment downstream and the storage of sediment within the channels.…”
Section: Introductionmentioning
confidence: 99%